Seagrass presence and absence in mangrove ghost forests in Moreton Bay, Australia - Twomey, Alice J; Remmerswaal, Amelia; Lovelock, Catherine E (PANGAEA, 2023)
Mangrove ecosystems across the globe face degradation due to severe climatic events, resulting in the formation of standing dead stems known as 'ghost forests'. This research project aimed to characterise the environmental parameters within mangrove ghost forests but also to ascertain their potential to support seagrass survival. Data was collected in three habitats (mangrove ghost forests, live mangroves and seagrass) at each of six study sites within Moreton Bay (Quandamooka), Queensland. Field data collection encompassed variables including air temperature, sea temperature, sediment grain composition, canopy coverage, turbidity, fetch length, and wave height (from north, north-east, and south-east directions). Additionally, within the ghost forests and live mangrove plots, data were gathered regarding stem density, diameter at breast height, the presence of seagrass wrack, presence of seagrass, the extent of seagrass coverage, and the specific species of seagrass. For the seagrass transects, data were gathered on seagrass presence, coverage, and species composition. The data collection process entailed three replicate plots within both the ghost forests and live mangrove forests, along with three replicate transects measuring 50 meters each within the seagrass meadows. This dataset shows that seagrass has colonised mangrove ghost forests and may be used to better characterise conditions within ghost forests. Data may be of interest to researchers in marine science, wetland ecology or restoration.
Keywords: ecosystem transitions; ghost forest; mangroves; Moreton Bay; Seagrass; sea-level rise